PENGARUH LIKUIDITAS, PRODUKTIVITAS, PROFITABILITAS, TERHADAP PERINGKAT SUKUK - Ratna Puji Astuti (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
The ranking of sukuk has an important meaning for the company ,financial ratios are used to see where the company rankings are included inboth rankings are investment grade . One of the reasons that made itattractive in the research on the rating agencies sukuk is the development ofIslamic finance is rapidly increasing, so that more sukuk has been done on theratings performance also makes bath Islamic financial institutions issuingsukuk . Sampling purposive sampling method used by the Sharia Boardcriteria (BUS) and Sharia (UUS) listed in the BI and have entered theranking Valuation found 6 companies . This research was conducted in theperiod 2008-2012. The data used is the data that has been published by eachcompany . The process of data analysis multiple regression analysis . Theresults showed that the Liquidity , Productivity and Profitability affect thesukuk ratings